1988
DOI: 10.1093/brain/111.6.1453
|View full text |Cite
|
Sign up to set email alerts
|

Sound Lateralization, Brainstem Auditory Evoked Potentials and Magnetic Resonance Imaging in Multiple Sclerosis

Abstract: Two tests of binaural hearing, namely intensity discrimination of alternating monaural clicks and interaural time difference (IATD) discrimination of binaural clicks, were performed in 28 patients with definite multiple sclerosis (MS) and 12 with an isolated brainstem lesion compatible with demyelination. Intensity discrimination defects were found in 53.5% and IATD defects in 82% of definite MS cases, although no overt auditory symptoms were reported and pure tone audiology was unremarkable. Corresponding fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Correlation with MRI abnormalities is plausible in some patients but anomalous in others [8], In the present study, the brainstem auditory-evoked responses were normal which suggests that the auditory pathways in the brainstem were not affected. The normal auditory brain stem response may also be due to an increased water content rather than demyelination [8].…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Correlation with MRI abnormalities is plausible in some patients but anomalous in others [8], In the present study, the brainstem auditory-evoked responses were normal which suggests that the auditory pathways in the brainstem were not affected. The normal auditory brain stem response may also be due to an increased water content rather than demyelination [8].…”
Section: Discussionsupporting
confidence: 43%
“…Correlation with MRI abnormalities is plausible in some patients but anomalous in others [8], In the present study, the brainstem auditory-evoked responses were normal which suggests that the auditory pathways in the brainstem were not affected. The normal auditory brain stem response may also be due to an increased water content rather than demyelination [8]. The electrodiag nostic tests (electroneurography and needle electromy ography) 3 weeks after the onset of the palsy explore indirectly the entire facial nerve, although electrical stimulation is performed distal to the stylomastoid fora men.…”
Section: Discussionsupporting
confidence: 43%
“…In both patients who could not utilize interaural time or intensity differences for the discrimination judgments, the BI component was absent. Van der Poel et al (1988) similarly observed that many MS patients have abnormal thresholds for detecting movement of a binaurally fused intracranial image using interaural timing differences.…”
Section: Introductionmentioning
confidence: 88%
“…In psychoacoustic tests, subtle defects have been recognised that mostly appear to reflect abnormalities of the subcortical auditory pathways. 44 Abnormalities of interaural time difference discrimination have been frequently reported, particularly in patients with known brainstem lesions, 45 and one study 46 found a large proportion of patients with MS who experienced difficulties with a task designed to test the temporal precedence effect in sound localisation. It is understandable that these defects are frequently associated with abnormalities of short latency AEPs, in which the measured conduction delays are of the same order as the temporal discrimination deficit.…”
Section: Discussionmentioning
confidence: 99%